Pendidikan Islam dalam perspektif kontemporer : Telaah konseptual dan tantangan implementasi - Amiruddin, Muhammad Wahyu (Maliki Interdisciplinary Journal, 2025)
This study is a literature review that examines the concept of Islamic education from a contemporary perspective by highlighting its objectives, principles, and implementation challenges in the modern era. Islamic education functions as a systematic effort to develop individuals who are morally grounded, knowledgeable, and civilized through the integration of revealed values and social realities. The findings indicate that Islamic education currently faces challenges related to globalization, modernization, and low levels of technology-based pedagogical literacy. Nevertheless, Islamic education has significant potential to foster character and ethical development through an integrated curriculum and well-directed digital transformation. This theoretical study concludes that Islamic education needs to strengthen an integrative approach, develop an adaptive curriculum, and enhance teacher competencies in order to respond effectively to contemporary challenges. In addition to identifying these challenges, this study proposes an integrative conceptual framework for Islamic education that places the value of tawhid as the foundational basis for curriculum development, pedagogy, and academic culture. This approach is considered relevant for strengthening the role of Islamic education in shaping Muslim generations that are adaptive, ethical, and competitive in the global era.